Targeting ferritin receptors for the selective delivery of imaging and therapeutic agents to breast cancer cells - Geninatti Crich, S. (2015)
In this work the selective uptake of native horse spleen ferritin and apoferritin loaded with MRI contrast agents has been assessed in human breast cancer cells (MCF-7 and MDA-MB-231). The higher expression of L-ferritin receptors (SCARA5) led to an enhanced uptake in MCF-7 as shown in T2 and T1 weighted MR images, respectively. The high efficiency of ferritin internalization in MCF-7 has been exploited for the simultaneous delivery of curcumin, a natural therapeutic molecule endowed with antineoplastic and anti-inflammatory action, and the MRI contrast agent Gd-HPDO3A. This theranostic system is able to treat selectively breast cancer cells over-expressing ferritin receptors. By entrapping in apoferritin both Gd-HPDO3A and curcumin, it was possible to deliver a therapeutic dose of 167 μg ml−1 (as calculated by MRI) of this natural drug to MCF-7 cells, thus obtaining a significant reduction of cell proliferation.